Development of Quiziz Media to Improve Learning Outcomes and Student Motivation in Islamic Religious Education Subjects at Integrated Islamic Middle Schools in Medan - Tasya Amelia Putri Siregar; Fahrur Rozy; Sindi Pramita; Ibnu Alwi Jarkasih Hrp; Asrul Daulay (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This project seeks to create interactive learning media using Quiziz to enhance educational results and student motivation in Islamic Religious Education (PAI) at Medan Integrated Islamic Junior High Schools. The used research methodology is research and development (R&D) using the 4D model (Define, Design, Develop, Disseminate). The examination of the first and subsequent field trials, conducted with a small sample of 9 students, yielded findings of 78.31% and 87.54%, respectively. Data were gathered via assessments of learning outcomes, motivation surveys, and observations throughout the educational process. The findings indicated that the use of Quiziz media substantially enhanced student learning outcomes. This is seen by a rise in the average performance of pupils after the implementation of this medium in comparison to prior use. Furthermore, student motivation for learning markedly improved, as seen by heightened active participation, excitement, and curiosity during educational activities.